Penentuan Harga Jual Untuk Menetapkan Laba Kotor Penjualan Paving Block dan Batako Pada Multazam Gending Kabupaten Probolinggo. - Seger Priantono (Fakultas Ekonomi Universitas Panca Marga, 2019)
Research conducted at the CV Multazam with the purpose to know the determination of sale price to determine the gross profit sales of paving block and brick making. Research in the form of variable costs of raw materials, direct labor, factory overhead costs, the cost of nonproduction. Methods of data analysis are the quantitative descriptive method. CV Multazam not yet classified the costs based on the function of the principal costs as the basis for determining cost of goods production, sale price calculation performed with make all expenses that occur divided by the amount of production, so there is no allocation factory overhead costs and the cost of non production to products paving block and brick making. The determination of the sale price with the method of cost-plus pricing generates gross profit per pc block paving products namely Rp 890,-and brick making Rp 845,- Keywords: Cost Plus Pricing Method, Gross Profit, Selling Price